Strengthening the Religious Dimension of the Local Subjects through Curriculum Context Analysis - Satrial, Ardi; Alfurqan, Alfurqan; Fitri, Nidya; Salim, Agus; Roza, Fauzi (TA`DIBUNA, 2026)
The purpose of this study is to analyze the context of local content curricula in vocational health schools with a religious dimension. A qualitative approach was chosen to examine this study through case studies at eight vocational health schools located in three provinces in Sumatra: West Sumatra, Riau, and Jambi. The study was conducted from 2023 to 2024. Data collection was conducted through interviews with nine informants, including school principals and vice principals, and through questionnaires completed by 27 respondents, comprising vocational, general, and religious subject teachers. Qualitative analysis was conducted by organizing data based on the implementation of local subjects in vocational health schools. The selected data were presented as visualized themes using a project map from NVivo 12 and a Google form chart diagram completed by teachers. This study found that the first step in developing a local subject is to conduct a curriculum context analysis, which includes education providers and user communities. The implications of this study can be used as a framework for developing a religious local subject in educational institutions.